2020
DOI: 10.1097/nmd.0000000000001244
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity and Personality Characteristics of Detained Adolescents With Delinquent Behavior

Abstract: The current study was undertaken with the aim of assessing the psychopathological symptoms, personality profile, and hostility in detained adolescents with delinquent behavior. A cross-sectional analytical study was carried out on 50 admitted adolescent delinquents in correctional institutes in the Greater Cairo region of Egypt. Results for delinquent adolescents were compared with age-equivalent adolescents with no history of delinquency. Both groups were subjected to the Adolescent and Adult Psychological St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…At the same time, the facts are presented that confirm the existence of differences in bullying among adolescents by gender, age and region (Man et al, 2022). It was proved that delinquent teenagers are aggressive and prone to conflict (Nasreldin et al, 2020), they have a pronounced propensity to break norms and rules, and low self-control (Mittal et al, 2021). The majority of juvenile delinquencies are explained by their antisocial traits: aggressiveness, proneness to conflict, and withdrawal (Abbaspour et al, 2022).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…At the same time, the facts are presented that confirm the existence of differences in bullying among adolescents by gender, age and region (Man et al, 2022). It was proved that delinquent teenagers are aggressive and prone to conflict (Nasreldin et al, 2020), they have a pronounced propensity to break norms and rules, and low self-control (Mittal et al, 2021). The majority of juvenile delinquencies are explained by their antisocial traits: aggressiveness, proneness to conflict, and withdrawal (Abbaspour et al, 2022).…”
Section: Discussionmentioning
confidence: 82%
“…This is a decreased psychosocial adaptation, low school performance, disruption of peer relationships, and deterioration of relations with parents (Song et al, 2022;Zhylin et al, 2022). Such juveniles are characterised by proneness to conflict, aggressiveness, and a high level of psychopathy (Nasreldin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such trends indicated that drivers with more extended driving experience who were experiencing neuroticism required more intensive follow-up investigation and interventions. To screen and identify individuals with high neurotic personality traits could be undertaken using a questionnaire such as the Eysenck personality Questionnaire, 131 or Five-Factory Inventory. 132 Additionally, a prevention logo or tips to warn about aggressive driving could be sent to targeted drivers using digital messages, such as Wei-chat messages in China.…”
Section: Discussionmentioning
confidence: 99%